2009
DOI: 10.1021/nl901774m
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Traction Force of a Single Cell by Aligned Silicon Nanowire Array

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 44 publications
7
113
2
Order By: Relevance
“…2D and S5). In contrast, bulk traction forces normally vary among different cell lines (20)(21)(22). Our observation suggests that there exists a common tension threshold value for the molecular tension generated by cells on an active integrin α V β 3 during adhesion.…”
mentioning
confidence: 71%
“…2D and S5). In contrast, bulk traction forces normally vary among different cell lines (20)(21)(22). Our observation suggests that there exists a common tension threshold value for the molecular tension generated by cells on an active integrin α V β 3 during adhesion.…”
mentioning
confidence: 71%
“…37 To investigate the force-displacement relationship of SiNWs with differing diameter, we measured lateral force by atomic force microscopy in contact mode, during which a constant force between the tip and SiNWs is applied, as shown in Figure 4a. 38 To deflect a SiNW with (Figure 4g).…”
Section: Resultsmentioning
confidence: 99%
“…Cancer cells invading other tissues form actin rich structures called invadopodia. 20 High protrusive forces are essential in order for cancer cells to metastasize and invade other tissues, 6 and future work will examine and quantify these forces in cancer cells. The technology presented here can potentially be useful for cancer diagnosis and in furthering understanding of the fundamental biological problems.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a change in the force a cell exerts on a surface could be an indication of disease; it has been reported that cancer cells exhibit a larger force than normal cells, by $ 20% to 50%. 6 Recent advances in microfabrication have enabled direct observation and quantitative analysis at the single cell level, thus providing accurate information that is helpful in explaining how cells function.…”
Section: Introductionmentioning
confidence: 99%